Pengaruh Pemanfaatan Aplikasi Dapodik Dan Kompetensi Operator Sekolah Terhadap Akurasi Data Pendidikan Pada SD Negeri Di Kota Bekasi - Mahmud; Krishantoro (Jurnal Ilmu Administrasi Publik, 2026)
This research was motivated by the existence of inaccuracies in educational data at public elementary schools in Kota Bekasi, such as discrepancies in student numbers, delays in updating teacher data, and data entry errors in the Data Pokok Pendidikan (Dapodik) system. Accurate educational data are essential as the basis for planning, budgeting, and evaluating educational policies. This study aims to analyze: (1) the influence of the utilization of the Dapodik application on the accuracy of educational data; (2) the influence of school operator competence on the accuracy of educational data; and (3) the simultaneous influence of the utilization of the Dapodik application and school operator competence on the accuracy of educational data at public elementary schools in Kota Bekasi. This research employed a quantitative approach using a survey method. The population consisted of 315 public elementary schools, with samples determined using probability sampling techniques. Data were collected through questionnaires that had been tested for validity and reliability. Data analysis was conducted using multiple linear regression with the assistance of SPSS software. The results indicate that: (1) the utilization of the Dapodik application has a positive and significant effect on the accuracy of educational data; (2) school operator competence has a positive and significant effect on the accuracy of educational data; and (3) the utilization of the Dapodik application and school operator competence simultaneously have a positive and significant effect on the accuracy of educational data atpublic elementary schools in Kota Bekasi. Therefore, the more optimal the utilization of Dapodik and the higher the competence of school operators, the higher the level of educational data accuracy. This study recommends strengthening technical training and assistance for school operators, optimizing the utilization of Dapodik features, and reinforcing data supervision policies by the Education Office to achieve effective, transparent, and accountable educational governance.